2021
DOI: 10.12688/f1000research.53803.3
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic and coagulopathy parameter as a survival predictor among moderate to severe COVID-19 patients in non- ICU ward: a single-center study at the main referral hospital in Surabaya, East Java, Indonesia

Abstract: Background : This research aimed to examine and analyze risk factors for death, hematologic parameters and coagulation in COVID-19 patients at RSUD Dr. Soetomo Surabaya, one of the referral centers for probable COVID-19 patient cases in East Java. Method : This was a retrospective analytical study by taking secondary data on patients with probable COVID-19 cases who were treated in hospital isolation rooms from May to September, 2020. Result : Of 538 probable COVID-19 patients, 217 were tested positive, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…11 Bintoro, et al (2021) reported in their study that there was an increase in APTT (albeit statistically insignificant) and a significant increase in prothrombin (p < 0.05) in a group of deceased patients. 12 This study found elevated coagulation factors, Ddimer, and fibrinogen values in moderate-severe COVID-19 patients, with mean ± SD 1172.14 ± 838.95 and 423.56 ± 88.91, respectively. This is caused by a series of cleaving in which proteolysis coagulation changes circulation and inactive factor becomes activated.…”
Section: Discussionmentioning
confidence: 50%
“…11 Bintoro, et al (2021) reported in their study that there was an increase in APTT (albeit statistically insignificant) and a significant increase in prothrombin (p < 0.05) in a group of deceased patients. 12 This study found elevated coagulation factors, Ddimer, and fibrinogen values in moderate-severe COVID-19 patients, with mean ± SD 1172.14 ± 838.95 and 423.56 ± 88.91, respectively. This is caused by a series of cleaving in which proteolysis coagulation changes circulation and inactive factor becomes activated.…”
Section: Discussionmentioning
confidence: 50%
“…The Kaplan-Meier curve in the results of their study showed a significant relationship between the mortality rate and the value of PT. Lower COVID-19 patient survival was significantly associated with prolonged PT values (>16 s) [27]. PT assesses the integrity of the extrinsic coagulation pathway and is influenced by the common pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have at least one comorbidity or more have poor clinical outcomes [ 7 ]. One of the most frequently observed laboratory abnormalities is a decreased lymphocyte count, which increases the risk of acute respiratory distress syndrome (ARDS) and, thus, the severity of the disease in COVID-19 patients [ 19 21 ].…”
Section: Discussionmentioning
confidence: 99%